2010
DOI: 10.1007/s12012-010-9082-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cardiopulmonary Effects of Size-Fractionated Ambient Particulate Matter in Mice

Abstract: A growing body of evidence from epidemiological and toxicological studies provides a strong link between exposure to ambient particulate matter (PM) of varying size and increased cardiovascular and respiratory morbidity and mortality. This study was designed to evaluate the cardiopulmonary effects of ambient coarse, fine, and ultrafine particles collected in Chapel Hill, NC. Mice were exposed to each size fraction by oropharyngeal instillation. Twenty-four hours later, pulmonary inflammation was assessed by br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 37 publications
9
48
1
Order By: Relevance
“…Further, ultrafine particles may directly interact with the cardiovascular system and affect vascular endothelium and atherosclerotic plaques as well as provoke local inflammation and oxidative stress. A study on mice (Tong et al, 2010) reported that hearts from mice exposed to ultrafine particles showed a significantly lower post-ischemic functional recovery and a greater infarct size, but no effects were seen for mice exposed to coarse particles (PM ranging from 2.5 to 10 m in aerodynamic diameter) or PM 2.5 . Indirect pollutant effects are supposed to evoke rather delayed and chronic cardiovascular responses.…”
Section: Mechanismsmentioning
confidence: 99%
“…Further, ultrafine particles may directly interact with the cardiovascular system and affect vascular endothelium and atherosclerotic plaques as well as provoke local inflammation and oxidative stress. A study on mice (Tong et al, 2010) reported that hearts from mice exposed to ultrafine particles showed a significantly lower post-ischemic functional recovery and a greater infarct size, but no effects were seen for mice exposed to coarse particles (PM ranging from 2.5 to 10 m in aerodynamic diameter) or PM 2.5 . Indirect pollutant effects are supposed to evoke rather delayed and chronic cardiovascular responses.…”
Section: Mechanismsmentioning
confidence: 99%
“…Thus, they are usually deposited in the tracheobronchial and alveolar regions of the airways (Lippmann et al, 1980). Due to the small size of PM 1 , these combustion derived particles can even penetrate through the lung tissue and reach the capillary blood vessels and circulating cells (Tong et al, 2010). Exposure to wood combustion-derived particles can lead to upregulation of proinflammatory cytokines, including interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α), as well as chemokines including IL-8 and keratinocyte-derived chemoattractant (KC).…”
Section: Research Articlementioning
confidence: 99%
“…Mercury in the air is easily taken up through the lungs, and about 74% of inhaled mercury is retained in human body (Syversen and Kaur, 2012). The mercury can be distributed throughout the human body via the blood circulation, which could cause cardiovascular and pulmonary health disease (Tong et al, 2010;Valera et al, 2012). Based on the Global mercury assessment 2013 reported by United Nations Environment Program (UNEP) (Assessment, 2013), the global mercury emissions to air from anthropogenic sources is estimated as 1960 t in 2010, but the emissions are changing in the range of 1010-4070 t. Atmospheric mercury exists primarily as gaseous elemental mercury (GEM-Hg°), reactive gaseous mercury (RGM-Hg 2 þ ) and particulate mercury Hg (p) (Fang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%